Quantity and quality of empathic responding by autistic and non-autistic adolescent girls and boys. (January 2021) - Rieffe, Carolien; O'Connor, Rachel; Bülow, Anne; Willems, Danique; Hull, Laura; Sedgewick, Felicity; Stockmann, Lex; Blijd-Hoogewys, Els
Empathy evokes support for the person in distress, and thus strengthening social cohesion. The question is to what extent empathic reactions can be observed in autistic adolescents and autistic girls in particular, since there is evidence that they have better social skills than boys, which might hinder their recognition as autistic. We examined 193 adolescents (autistic/non-autistic boys/girls) during an in vivo task in which the experimenter hurt herself. In line with our predictions, no group or gender differences appeared related to their attention for the event; yet autistic girls and boys showed less visible emotional arousal, indicative of less affective empathy. Autistic girls and boys reacted by comforting the experimenter equally often as their non-autistic peers, but autistic boys seemed to address the problem more often than any other group; while girls (autistic and non-autistic) more often addressed the emotion of the person in need. Our findings highlight that empathic behaviour – to some extent – seems similar between autistic and non-autistic boys and girls. However, differences exist, in terms of expressed emotional arousal and gender-specific comforting styles. Autistic girls' higher levels of emotion-focused comforting could be explained by well-developed social skills, camouflaging, or emotional investment in relationships with others. Lay abstract: Empathy is an important feature to feel for another person, evoking social support for the person in distress, and thus strengthening social cohesion. The question is to what extent empathic reactions can also be observed in autistic adolescents and autistic girls in particular, since their often mentioned good social skills might prevent their direct social environment from recognizing their autism. We examined 194 adolescents (autistic and non-autistic boys and girls) during an in vivo task in which the experimenter pretended to hurt herself while closing a binder. All responses by the participants were videotaped and coded by two independent coders. In line with our predictions, no group or gender differences appeared related to their attention for the event; yet autistic girls and boys showed less visible emotional arousal, which could indicate less affective empathy (feeling for someone), or which could indicate that autistic adolescents know less well how to show empathy. Autistic girls and boys reacted by comforting the experimenter equally often as their non-autistic peers, but autistic boys addressed the problem more often than any other group, while girls (autistic and non-autistic) more often addressed the emotion of the person in need. Our findings highlight that empathic behaviour is remarkably similar between autistic and non-autistic boys and girls. Indeed, only subtle differences exist, in terms of expressed emotional arousal and gender-specific comforting styles. Autistic girls' higher levels of emotion-focused comforting could be explained by well-developed social skills, camouflaging, or emotional investment in relationships with others.